FOMO (Fear of Missing Out) di Kalangan Gen-Z: Jasa Titip Dubai Chocolate sebagai Peluang Baru bagi UMKM Indonesia Studi Kasus Sosial Media - Vera Maria; Vina Nailatul Nabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Gen-Z has grown alongside rapid technological and digital media development, fostering frequent virtual interactions over face-to-face ones. This shift often triggers Fear of Missing Out (FOMO), where individuals feel anxious about missing trends or updates. Among Gen-Z, FOMO is strongly influenced by social media, driving consumptive behavior. This article explores how FOMO creates opportunities for Indonesian Micro, Small, and Medium Enterprises (MSMEs) through jasa titip (personal shopping services). Using the Dubai Chocolate trend as a case study, it highlights how social media-driven demand has spurred interest in personal shopping services to source and deliver such products. The research emphasizes the importance of social media as a tool for MSMEs to tap into FOMO-driven markets. It also encourages MSMEs to innovate by offering affordable, locally sourced alternatives to remain competitive. This approach enables MSMEs to thrive in a dynamic, trend-focused digital landscape.